Risk versus regulation: an update on the state of e‐cigarette control in Australia. Issue 1 (24th January 2019) - Morgan, Jody; Breitbarth, Andreas K.; Jones, Alison L.
Abstract: E‐cigarettes are increasingly common around the world, particularly among youth. Ingestion of nicotine‐containing e‐liquid, while relatively rare, is the major toxicological risk associated with their use. Current Australian regulation has nicotine for use in e‐cigarettes listed as a dangerous poison in Schedule 7, with its supply or sale illegal in all states and territories, while regulation on the sale of e‐cigarettes and accessories varies by state. However, with increasing evidence that e‐cigarettes produce far fewer toxic by‐products than their combustible counterparts perhaps it is time to review this regulation.